Micropatterned substrates for studying astrocytes in culture - Lee, William; Parpura, Vladimir (Frontiers in Neuroscience, 2009)
Recent studies of the physiological roles of astrocytes have ignited renewed interest in the functional significance of these glial cells in the central nervous system. Many of the newly discovered astrocytic functions were initially demonstrated and characterized in cell culture systems. We discuss the use of microculture techniques and micropatterning of cell-adhesive substrates in studies of astrocytic Ca2+ excitability and bidirectional neuron-astrocyte signaling. This culturing approach aims to reduce the level of complexity of the system by limiting the interacting partners and by controlling the localization of cells. It provides tight control over experimental conditions allowing detailed characterization of cellular functions and intercellular communication. Although such a reductionist approach yields some difference in observations between astrocytic properties in culture and in situ, general phenomena discovered in cell culture systems, however, have also been found in vivo.